THE EFFECT OF GREEN MARKETING AND BRAND IMAGE TOWARD PURCHASE DECISIONS ON SENSATIA BOTANICALS PRODUCTS IN JAKARTA - Sollu, Yolanda; Hendratmoko (Moestopo International Review on Social, Humanities, and Sciences, 2024)
Environmental issues have become a major focus in many countries, including Indonesia, where pollution, climate change, and biodiversity loss are significant challenges. The increasing public awareness of the negative impact of environmental issues companies like Sensatia Botanicals to implement green marketing strategies. The purpose of this study is to examine the effect between green marketing and brand image toward purchase decisions on Sensatia Botanical products in Jakarta. The research method used is quantitative research method. The number of respondents in this study were 150 respondents, namely consumers who have purchased Sensatia Botanicals products who live in Jakarta. The sampling technique was non-probability sampling using a questionnaire containing several statements and given to research subjects online using the google form format. The analysis method uses Multiple Linear Regression Analysis with the SPSS 26 program. The study's result demonstrates that there is a significant and positive effect between green marketing toward purchase decisions on Sensatia Botanicals products in Jakarta, and there is a significant and positive effect between brand image toward purchase decisions for Sensatia Botanicals products in Jakarta.